What is the Nature of Palliative Care for Patients Dying from Heart Failure on Acute Hospital Wards? A Critical Review. - Helme, Laura (2008)
A critical review was conducted with an aim to explore the nature of palliative care for patients dying from heart failure. A thorough search of healthcare databases, specific journals and relevant websites produced the literature that provided the basis for this review. All literature was critically appraised and categorised into chapter topics.